VWFpp/ADAMTS13 ratio is a useful marker of postliver transplantation thrombotic microangiopathy: A pediatric case report. Issue 1 (10th December 2019) - Duquenne, Lisa; Balbeur, Samuel; Everard, Emilie; Reding, Raymond; Eeckhoudt, Stéphane; Brichard, Bénédicte; Godefroid, Nathalie; Derycke, Emilien; Komuta, Mina; Scheers, Isabelle; Smets, Françoise; Sokal, Etienne; et al.
Abstract: vWFpp/ADAMTS13 ratio should be further studied as a useful marker for diagnosis of thrombotic microangiopathy postliver transplantation. Immunosuppressive regimen modification and plasma supplementation can lead to recovery. Abstract : vWFpp/ADAMTS13 ratio should be further studied as a useful marker for diagnosis of thrombotic microangiopathy postliver transplantation. Immunosuppressive regimen modification and plasma supplementation can lead to recovery.